PENGARUH DISIPLIN DAN MOTIVASI BELAJAR PESERTA DIDIK TERHADAP PRESTASI BELAJAR EKONOMI KELAS X MIA DI SMA NEGERI 10 PEKANBARU - Hartini, Siti; Suarman, Suarman; Kartikowati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This study aims to determine the effect of student discipline and learning motivation to the achievement in economic learning of student in public high school 10 Pekanbaru. This study uses quantitative appoach method and the population in this study is students grade X MIA which amounted to 108 people and the sample obtained 85 respondens using proportional random sampling technique. Data analysis techniques used are Descriptive Analysis and Multiple Linear Regression Analysis with the help of SPSS version 16.0. The result of this research is the discipline learning have an effect on significantly to student achievement which obtained tcount 4,726> ttabel 1,663 and significant value 0,000 <0,05. Motivation learning significantly effected to student in learning achievement which obtained tcount 2,459> ttabel 1,663 and significant value 0,000 <0,05. Simultaneously there is a significant influence between learning discipline and student learning motivation with learning achievement where obtained value fhitung 30,266> ftabel 3,11 and significant value 0,000 <0,05. Multiple linear regression equation obtained in this research is Y = 41,466 + 0,351X1 + 0,220X2. The results of this study showed that the discipline and learning motivationbe affected to learning achievement on economic subjects student class X mia SMA Negeri 10 Pekanbaru. It’s means that the higher of discipline and motivation to learn will improve student in achievement learning. For increasing the learning achievement of studentis need a support from teachers and themselves in the form of discipline and motivation.Keywords: Learning Discipline, Learning Motivation, Learning Achievement